Analysis And Design Enterprise Architecture Using Togaf Adm In Account Team And Sales And Marketing Support Division Of Pt. Inti (persero) - Afifah Nurul Izzati; Yuli Adam Prasetyo; Rahmat Mulyana (eProceedings of Engineering, 2016)
PT Industri Telekomunikasi Indonesia (Persero) or abbreviated PT. INTI is one of the State Owned Enterprises (SOEs) engaged in the telecommunications industry. PT. INTI in 2016 plans to change the business focus of the company distributor telecommunication equipment into a manufacturing company that provides products of telecommunications equipment. Thus, PT.INTI must develop the marketing and sales process, so PT. INTI can provide the best service, and competes with other leading provider of products telecommunications equipment. The marketing activities and sales process relate with account team and sales and marketing support. To increase the sales and develop the marketing, account team and sales and marketing support need design of enterprise architecture including integration between business architecture, data architecture or information, application architecture, and technology architecture . To support the design of enterprise architecture in this study will require a framework. Framework used is TOGAF ADM focusing Preliminary architectural design phase, Architecture Vision, Business Architecture, Information System Architecture, Technology Architecture, Opportunities and Solution Architecture . The result of this research are gap analysis, business architecture blueprint, data architecture blueprint, application architecture blueprint, and technology architecture blueprint, and IT roadmap. This result can be recommendation for account team and sales and marketing support to improve their service and performance. Keywords: Manufacturing Company, Enterprise Architecture, Account Team, Sales and Mareting Support, TOGAF ADM